Attenuation of gentamicin-induced nephrotoxicity in rats by fleroxacin. - Beauchamp, D (1997)
The effect of fleroxacin on gentamicin-induced nephrotoxicity was evaluated with female Sprague-Dawley rats. Animals were injected during 4 or 10 days with saline (NaCl; 0.9%), gentamicin alone at doses of 10 and 40 mg/kg of body weight/12 h (subcutaneously), fleroxacin alone at a dose of 25 mg/kg/12 h (intraperitoneally), or the combination gentamicin-fleroxacin in the same regimen. Gentamicin induced a dose- and time-dependent renal toxicity as evaluated by gentamicin cortical levels, sphingomyelinase activity in the renal cortex, histopathologic and morphometric analysis, blood urea nitrogen and serum creatinine levels, and cellular regeneration ([3H]thymidine incorporation into DNA of cortical cells). The extent of these changes was significantly reduced when gentamicin was given in combination with fleroxacin. Although the mechanisms by which fleroxacin reduces the nephrotoxic potential of gentamicin are unknown, we propose that the fleroxacin-gentamicin combination enhances exocytosis activity in proximal tubular cells, as suggested by the higher excretion of urinary enzymes and lower cortical levels of gentamicin observed in animals treated with the combination fleroxacin-gentamicin compared with those treated with gentamicin alone. The protective effect of fleroxacin on gentamicin nephrotoxicity should be investigated further.